Evaluation of Phosphorus Source and Chelate Application as Starter Fertilizer in Corn - C. L. Edwards; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2016)
The differences between common phosphorus (P) fertilizers as a starter in corn production have been studied for many years. However, little research has been conducted showing which P fertilizer sources are most effective with varying compositions of ortho- and poly-phosphate. The objectives of this study were to evaluate three commercially available P fertilizers, 0-16-19, 10-34-0, and 0-18-18 (N-P2O5-K2O) as starter band with and without the addition Cee*Quest-70 (CQ-70), a glucoheptonate chelate. The study was conducted at two locations, Scandia and Rossville, in 2014 and 2015. Experimental design was a randomized, complete block with four replications and a factorial treatment arrangement. Whole plant corn tissue samples were taken at V-6 and weighted for biomass. Tissue samples were analyzed for P. Yield, V-6 biomass, and V-6 P uptake were analyzed for treatment differences. Results show that there were no yield differences between P fertilizers with or without the addition of CQ-70. Phosphorus fertilizer was found to have a significant effect on P V-6 tissue concentration at the Rossville location. However, there was no effect on P uptake. Fertilizer source was found to have a significant effect on V-6 biomass and P uptake.
Keywords: phosphorus; corn; starter; fertilizer; soil; chelating agents